Organisation and institution: a review of Selznick's traditional institutionalism and new institutionalism - Quddus, S. M. Abdul (The University of Chittagong Press, 2005)
In modern societies, the elements of rationalized formal organization are deeply ingrained in, and reflect, widespread understandings of social reality. Many of the positions, policies, programmes and procedures of modern formal organizations are enforced by public opinion, by laws etc. Such elements of formal organizations are manifestations of powerful 'institutional' rules which function as highly rationalized 'myths' that are binding in particular organizations. This paper tends to examine Philip Selznick's view on 'organization' and 'institution' as he is regarded as the pioneer of the institutional theory of organization as well as other existing alternative approaches of organization and institution discussed by contemporary scholars in the area of organization study. This paper also tries to explain two basic terms of organization theory i.e.'organization' and 'institution' from the perspectives of traditional institutionalism vs. new institutionalism more generally to account for clarifying the differences between the two.